Structure and biosynthesis of fungal cell walls: methodological approaches - Farkas, V (Folia microbiologica, 2003)
Fungal cell walls possess a characteristic chemical composition differentiating fungal cells from other cell types. For this reason, the mechanisms involved in cell-wall formation represent a potential target for selective antifungal drugs. Understanding the structure and biosynthesis of fungal cell walls opens the ways for design of effective drugs for treating fungal diseases. This article reviews the history methods employed in chemical and structural analysis of fungal cell walls and in studies concerning their formation.
Keywords: mykologie; molekulární biologie; buněčná stěna; houby; biochemie; Microscopy; Molecular Biology; Mycology; Biochemistry; Fungi; Cell Wall; mikroskopie